Experimental and analytical fatigue data for notched shafts in bending - Ali-Reza Gowhari-Anaraki; Hardy, Stephen John; Mohammad Kazem Pipelzadeh (2003)
An experimental investigation has been carried out on two types of shaft with different stress concentration features in order to determine the notched members fatigue life in bending. The shafts are made from steel with DIN specification CK45, which is widely used for machinery components. These lives are compared with estimates using the simple notch-stress-strain- conversion rules (e.g., Neuber; Linear) and the strain energy density methods in conjunction with the Coffin-Manson strainlife relationship. The paper demonstrates the simplicity and accuracy of the approach although the predictive capability was found to depend on the magnitude of the elastic stress concentration factor